Effect of Storage Temperatures on Physico-Chemicals, Phytochemicals and Antioxidant Properties of Watermelon Juice (Citrullus lanatus) - Nur Shafinaz Mohamad Salin; Wan Mazlina Md Saad; Hairil Rashmizal Abdul Razak; Fatimah Salim (Metabolites, 2022)
Watermelon (Citrullus lanatus) consists of high moisture content and is favoured for its juice products. The popular fruit has a tempting taste, sweet aroma and attractive flesh colour. It is enriched with phytochemicals and antioxidant properties that are beneficial to human health. Due to convenience, the majority of individuals are likely to consume watermelon juice. However, little is known about the fruit juice storage and temperatures that may affect its beneficial properties. This study investigated the effect of storage temperature at room temperature, refrigerator cold, refrigerator freeze and freeze-dried, and analyzed the juice physico-chemicals (weight loss, pH, ash, moisture, total soluble solid, browning and turbidity), phytochemicals (total phenolic, total flavonoid, lycopene and β-carotene) and antioxidant scavenging activities during 9 days of storage. The results showed that watermelon juice was affected by storage temperatures and conditions with significant changes in physico-chemical appearance and decrease in total phytochemical content, thus consequently affecting their antioxidant activities during 9 days of storage. Although fresh watermelon juice can be consumed for its high nutritional values, freeze-drying is the preferable technique to retain its benefits and to delay juice degradation.